Transcranial direct current stimulation for treatment of freezing of gait: A cross‐over study. Issue 8 (30th April 2014) - Valentino, Francesca; Cosentino, Giuseppe; Brighina, Filippo; Pozzi, Nicolò Gabriele; Sandrini, Giorgio; Fierro, Brigida; Savettieri, Giovanni; D'Amelio, Marco; Pacchetti, Claudio
ABSTRACT Background and objective Progression of Parkinson's disease (PD) is frequently characterized by the occurrence of freezing of gait (FOG) representing a disabling motor complication. We aim to investigate safety and efficacy of transcranial direct current stimulation of the primary motor cortex of PD patients with FOG. Methods In this cross‐over, double‐blind, sham‐controlled study, 10 PD patients with FOG persisting in "on" state underwent anodal and sham direct current stimulation for 5 consecutive days. Clinical assessment over a 1‐month period was performed. Results A significant improvement of gait, as assessed by the Stand Walk Sit test, with reduction in number and duration of FOG episodes, along with a significant reduction in the Unified Parkinson's Disease Rating Scale score, were observed after anodal stimulation. Beneficial effects were more evident after the entire 5‐day stimulation session, and persisted until the end of the observation period. Conclusions Anodal transcranial direct current stimulation of the motor cortex is safe and has therapeutic potential in PD patients with FOG. © 2014 International Parkinson and Movement Disorder Society